2004
DOI: 10.1111/j.1523-1755.2004.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycosylation end products induce inducible nitric oxide synthase (iNOS) expression via a p38 MAPK-dependent pathway

Abstract: These data suggest that cytokine release, NF-kappaB and p38 MAPK-dependent pathways may play a role in AGE-induced iNOS expression and subsequent nitric oxide production in mesangial cells. Rosiglitazone may prevent AGE-induced iNOS expression by interfering with p38 MAPK activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 41 publications
3
59
0
1
Order By: Relevance
“…Currently, to our knowledge, there are no literature data related to RAGE involvement in ßA nitrergic system activation; however, it has been demonstrated that RAGE linkage with other ligands, as advanced glycation-end products (AGE), stimulated iNOS expression in mouse macrophages (37), in murine endothelial cells (38), and in murine macrophages (39). AGE stimulation led to nitrite accumulation and iNOS protein expression, which were partially downregulated by preincubation with anti-RAGE antibody, suggesting the role of RAGE in AGE-induced nitrosative stress activation (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, to our knowledge, there are no literature data related to RAGE involvement in ßA nitrergic system activation; however, it has been demonstrated that RAGE linkage with other ligands, as advanced glycation-end products (AGE), stimulated iNOS expression in mouse macrophages (37), in murine endothelial cells (38), and in murine macrophages (39). AGE stimulation led to nitrite accumulation and iNOS protein expression, which were partially downregulated by preincubation with anti-RAGE antibody, suggesting the role of RAGE in AGE-induced nitrosative stress activation (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular responses unleash important physiological effects, such as being a potent vasodilator with effects on both blood pressure regulation and renal function 2,54 . Recent studies have shown that AGEs induce iNOS expression in mesangial cells by activation of cytokines 2 -NF-kB and p38 MAPK 54,56 . Mesangial cells cultured in high glucose medium showed an increase in iNOS expression related to expansion of extracellular fibronectin 52,53,55 .…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…Moreover, its accumulation is involved in early and in late-stage renal disease 52,54 . Nitric Oxide has a very short half-life and is formed from L-arginine, in an oxidation reaction catalyzed by three nitric oxide synthases isoforms (NOS) 55,56 . Two NOS are calcium dependent, one expressed in endothelial cells (eNOS) and the other in neuronal cells (nNOS).…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Overproduction and accumulation of AGEs having a key role in aging has been shown to result in several structural and functional disorders [2,3]. Production of AGEs depends on the blood glucose concentration and the exposure time and may result directly from the hyperglycemia [4].…”
Section: Introductionmentioning
confidence: 99%